Synthesis, characterization and photo-catalytic activity of guar-gum-g-aliginate@silver bionanocomposite material. Issue 13 (24th February 2020) - Hasan, Imran; Khan, Rais Ahmad; Alharbi, Walaa; Alharbi, Khadijah H.; Abu Khanjer, Maymonah; Alslame, Ali
Abstract : The green mechanism for the synthesis of nanoparticles and their application to the wastewater treatment is of inordinate curiosity to the research community. Abstract : The green mechanism for the synthesis of nanoparticles and their application to the wastewater treatment is of inordinate curiosity to the research community. Herein we outline a novel method for the synthesis of silver nanoparticles via a green route using alginate-guar gum blend (GG-Alg@Ag) and their application to degrade methylene blue (MB) dye. The synthesized material was characterized by FTIR, XRD, SEM-EDX, TEM, TGA-DTG, AFM, and UV-vis techniques. A combination of RSM and CCD was employed to compute the system and optimized values of various interacting parameters such as exposure time (120 min), pH (4.98), dye concentration (194 mg L −1 ), and catalyst dose (0.07 g) with a photodegradation capacity of 92.33% and desirability 1.0. The mechanism of degradation reaction was best elucidated by the pseudo-second-order model suggesting chemical deposition of MB on the GG-Alg@Ag surface through followed by the reduction mechanism in the occupancy of visible light. The optical studies indicated a value of 2.5 eV by Tauc's plot for bandgap energy ( E g ) for GG-Alg@Ag bionanocomposite.